COMPREHENSIVE RADIATION DIAGNOSIS OF OSTEOARTHROSIS OF THE KNEE JOINT IN THE EARLY STAGES - Avezova Sh. Sh; Madumarova Z. Sh.; Zulunov A. T.; Yakubov N. I. (Web of Journals Publishing, 2024)
Osteoarthrosis (OA) is a chronic joint disease characterized by primary degeneration of articular cartilage, a change in the structure of subchondral bone with the formation of new bone structures (osteophytes), the development of an inflammatory process in the synovial membrane (synovitis) and damage to periarticular soft tissues. According to modern concepts, OA has a multifactorial genesis, which is based on a violation of the balance of degradation and synthesis within articular cartilage and subchondral bone, which in turn leads to cartilage destruction and characteristic changes in subchondral bone. Among all degenerative joint diseases, OA accounts for 12.3%, i.e. it is slightly inferior to the entire group of inflammatory joint diseases, which currently accounts for 17.7%.
Keywords: osteoarthrosis, metabolism of cartilage, T2 relaxometry, multiplex assay.